Morphology of conducting polymeric coatings: quantitative comparison between theory and experiment - Lin, B.; Sureshkumar, R.; Kardos, J.L. (Chemical engineering science, 2003)
The density profile of electrosynthesized polymeric layers on carbon fibers is obtained from gravimetric and scanning electron microscopy (SEM) data. The coating density ρ is found to decrease with increasing radial distance, r, subject to the power law ρ(r)∝1/ r . Based on a modified diffusion-limited aggregation (DLA) model, it is shown that lattice Monte Carlo simulation of the coating process predicts the experimentally observed power law exponent.